ROLE RELATION NEGOTIATION BETWEEN NATIVE SPEAKER AND INDONESIAN EFL-LEARNER IN AN ENGLISH CASUAL CONVERSATION - Sunardi Sunardi (Universitas Sebelas Maret, 2012)
Dialogue is the means language gives us for expressing interpersonal meanings about roles and attitudes. Being able to take part in dialogue means being able to negotiate the exchange of interpersonal meanings and being able to realize social relations with other language users. This study aims at describing the patterns of role relation negotiation as the realization of interpersonal meaning in an English casual conversation between native speaker (NS) and Indonesian EFL-learner (NNS). The patterns were studied through the choice of speech functions when the interactants act on each other. The results of this study show that NNS plays his role as initiator, while NS as supporter; the conversation is the one of information negotiation rather than goods and services negotiation. Key words: casual conversation, interpersonal meaning, role relation negotiation, speech function